Magnitude of cancer-associated thrombosis in Africa: A systematic review and meta-analysis - Astewle Andargie Baye; Agimasie Tigabu; Yirgalem Abere; Birara Ayichew Tilaye; Demewoz Kefale; Lakachew Yismaw Bazezew; Birhanu Mengist Munie; Berihun Bantie; Abebu Tegenaw Delie; Dessalegn Haile (iScience)
Summary: Comprehensive data on the epidemiology of cancer-related thrombosis in Africa has been sparse until recently. Thus, this review was aimed to investigate the magnitude of cancer-related thrombosis in Africa. To obtain key articles, comprehensive search was conducted using various databases. A random-effects model was used to determine the pooled magnitude. Heterogeneity across the studies was checked, and publication bias was determined. The pooled magnitude of thrombosis among cancer patients in Africa is 11.65% (95% confidence interval [CI]: 9.02–14.28). Advanced age, comorbidity, and level of D-dimer were the factors associated with cancer-associated thrombosis.Cancer-related thrombosis has become a significant public health burden in Africa. About 3 out of 25 cancer patients are at increased risk of acquiring thrombosis. It is better to provide training and capacity-building programs for healthcare providers in Africa on the prevention, diagnosis, and management of cancer-related thrombosis and develop standardized evidence-based multidisciplinary approach care guidelines.